2021
DOI: 10.1111/anu.13215
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation increases the potential of fishmeal replacement by soybean meal in diets for largemouth bass Micropterus salmoides

Abstract: The effects of replacing dietary fishmeal by soybean meal with taurine supplementation on feed intake, growth, feed utilization, body composition and waste output of largemouth bass were examined. A control diet (C) contained 400 g/kg fishmeal, 20%, 40% and 60% of fishmeal in diet C was replaced by soybean meal, with or without 5 g/kg taurine supplementation (abbreviated as S20 + T, S40 + T, S60 + T, S20, S40 and S60, respectively). Significantly lower weight gain was found in fish fed diet S60 compared with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…In contrast, results from Li et al (2021a) suggested that with a blend of poultry by-product meal, soybean meal, krill shrimp meal, and blood meal as a fish meal alternative, the percent weight gain of Largemouth Bass declined significantly when fed a 14.5% fish mealbased diet (containing 0.32% taurine) compared to that in fish receiving the control diet (containing 65.3% fish meal and 0.58% taurine); supplementation of 0.5% taurine tended to increase the growth of fish, but no significant effect was observed. Wu et al (2021a) utilized soybean TAURINE SUPPLEMENTATION IN LARGEMOUTH BASS meal to substitute graded levels of dietary fish meal for Largemouth Bass, and their results indicated that fish began to decrease when dietary fish meal was reduced from 32% to 24%, with the dietary taurine concentration reduced from 0.226% to 0.180%, which implied that keeping the dietary taurine concentration at 0.226% is sufficient to maintain the normal growth of fish. Therefore, we speculate that the difference in effects of taurine on Largemouth Bass between the current study and the Li et al (2021a) study might be ascribed to the fact that taurine deficiency was not the limiting factor influencing the growth of Largemouth Bass that were fed the 14.5% fish meal-based diet containing 0.32% taurine in the study from Li et al (2021a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, results from Li et al (2021a) suggested that with a blend of poultry by-product meal, soybean meal, krill shrimp meal, and blood meal as a fish meal alternative, the percent weight gain of Largemouth Bass declined significantly when fed a 14.5% fish mealbased diet (containing 0.32% taurine) compared to that in fish receiving the control diet (containing 65.3% fish meal and 0.58% taurine); supplementation of 0.5% taurine tended to increase the growth of fish, but no significant effect was observed. Wu et al (2021a) utilized soybean TAURINE SUPPLEMENTATION IN LARGEMOUTH BASS meal to substitute graded levels of dietary fish meal for Largemouth Bass, and their results indicated that fish began to decrease when dietary fish meal was reduced from 32% to 24%, with the dietary taurine concentration reduced from 0.226% to 0.180%, which implied that keeping the dietary taurine concentration at 0.226% is sufficient to maintain the normal growth of fish. Therefore, we speculate that the difference in effects of taurine on Largemouth Bass between the current study and the Li et al (2021a) study might be ascribed to the fact that taurine deficiency was not the limiting factor influencing the growth of Largemouth Bass that were fed the 14.5% fish meal-based diet containing 0.32% taurine in the study from Li et al (2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the enzymes involved in taurine generation from its precursor amino acids are either present at low concentration or missing in some fish species, leading to a poor biosynthetic capacity of taurine (Hano et al 2017). Previous studies indicated that when carnivorous fish were fed diets with a high soy protein inclusion level, supplementation of taurine improved growth performance and feed utilization in numerous species, such as Cobia Rachycentron canadum (Lunge et al 2007), Madai Pagrus major (Matsunari et al 2008), Turbot Scophthalmus maximus (Yun et al 2012), Black Porgy Acanthopagrus schlegeli (Kalhoro et al 2020), and Largemouth Bass (Wu et al 2021a). Considering that plant protein ingredients contain lower sulfur amino acid concentrations relative to animal protein ingredients (Spitze et al 2003;Li et al 2021b;Wu et al 2021a), the addition of taurine may be an approach to improve growth and feed utilization in fish that are fed a low fish meal diet with a high soy protein inclusion level.…”
mentioning
confidence: 99%
See 3 more Smart Citations